PERANCANGAN MULTIMEDIA INTERAKTIF KEJAYAAN KERAJAAN PAKUAN PAJAJARAN - Setiadi, Rali (LPPM BSI Bandung, 2015)
ABSTRACTIn West Java, the opportunity for kids to get knowledge history of the ancestors is very rare, And then how to give back the values of nationalism among the young generation in West Java traced back to the issue of preservation and continuation of the nations history, and how to preserve the story of Pakuan Pajajaran and be continue to the next generation. Until this study, the authors tried to make design of interactive multimedia Kingdom of Pakuan Pajajaran characteristics and identity of wisdom local culture of Sunda. as a means of introduction to the history of the primary school students. With illustrations of authors try to explain and tell the history of the present, in order to provide moral message contained within the history.Keywords: Multimedia, Interactive, History, Pakuan Pajajaran.Â ABSTRAKDi Jawa Barat kesempatan anak-anak untuk mengenal sejarah leluhur sangat jarang, Bagaimana mengembalikan nilai nasionalisme dikalangan generasi muda di Jawa Barat dirunut kepada persoalan pelestarian dan penerusan sejarah bangsa, lalu bagaimana melestarikan kisah Pakuan Pajajaran serta diteruskan turun temurun kepada generasi berikutnya. Melalui penelitian ini, penulis mencoba merancang multimedia interaktif Kerajaan Pakuan Pajajaran ciri khas identitas lokal Tatar Sunda. sebagai sarana pengenalan sejarah pada siswa sekolah dasar. Dengan ilustrasi penulis mencoba memaparkan dan menceritakan sejarah yang ada, guna memberikan pesan moral yang terkadung dalam sejarah tersebut.Kata kunci: Multimedia, Interaktif, Sejarah, Pakuan Pajajaran